Identification of the mutation in nphs1 gene in a patient with congenital nephrotic syndrome - Kim Liên, Nguyễn Thị; Đếm, Phạm văn; Hương, Nguyễn Thu; Quỳnh Hương, Nguyễn Thị; Dương, Phạm Thùy; Hoàng, Nguyễn Huy (Vietnam Journal of Biotechnology, 2018)
Congenital nephrotic syndrome (CNS) is a rare and severe disease, is inherited as an autosomally recessive trait. CNS occurs predominantly in families of Finnish origin and manifests shortly after birth but now it has been observed in all countries and races with an estimated incidence of 1.2 cases per 10,000 live births. CNS patients have gradually impaired renal function, renal failure occurred ascending, and rapidly progressed to end-stage renal disease. Untill now, the disease has had without specific treatment, medical mostly corticosteroid therapy to anti-inflammatory and immuno suppressive and await a kidney transplant. Mutations in NPHS1 gene, which encodes nephrin protein, are known to be the main causes of congenital nephrotic syndrome in the patients. The NPHS1 protein plays an important role in ensuring glomerular filtration activities and mutation analysis in NPHS1 gene becomes the gold standard for diagnosis for CNS. In this study, for the first time in Vietnam, we performed mutational analysis of NPHS1 in a patient. The patient was admitted in the Department of Pediatrics, Vietnam National Hospital of Pediatrics and was diagnosed with congenital nephrotic syndrome. All 29 exons and exon/intron boundaries of NPHS1 gene of patient and his parents were analyzed using PCR and DNA sequencing. Genetic analysis of the NPHS1 gene revealed compound of one heterozygous variant p.E117K (exon 3), one heterozygous missense mutation p.D310N (exon 8) and one heterozygous frame-shifting mutation (c.3250_3251insG causing p.V1084GfsX12 in exon 24) in patient. Mutation analysis in NPHS1 gene in parents showed that polymorphism p.E117K and mutation p.D310N were found in healthy father and mutation p.V1084GfsX12 was found in healthy mother.